Optimization of Energy Efficiency and Hatchability Rates in IoT-Based Egg Incubators - Muhammad Ferdiansyah; Lika Mariya; Siti Kholifah K (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
This study aims to develop an Internet of Things (IoT)-based egg incubator integrated with renewable energy to enhance operational efficiency and hatching success rates. The system utilizes an ESP32 microcontroller to regulate temperature and humidity automatically, with a 100 Wp solar panel as the primary energy source. Testing results demonstrate that the IoT-based system maintains optimal temperature and humidity levels more effectively than conventional systems, achieving a 92% hatching success rate, which surpasses the 85% success rate of traditional incubators. Additionally, the integration of solar panels reduces dependency on conventional electricity and lowers operational costs by 30%, making it a more energy-efficient and sustainable solution. These findings highlight the potential of combining IoT automation and renewable energy to improve production efficiency, reduce costs, and support sustainable livestock management. The success of this system paves the way for further advancements in IoT and renewable energy applications in the agricultural sector, with potential scalability for both small-scale farmers and large-scale poultry industries, fostering digital transformation in more efficient and eco-friendly food production.